(3eLehYI aj GdcjejGAs
(3ChdgG (B:s
(3Ef QCS GdJOHjQ heGe GdCeQ hLfS GdONGf ai cd JUYjO hefg GdQjM ai ONhd GdCfjI s
(3BNQgG (B:s
(3aEPG CQOJ WQjbI GdhQb adjcf fGQc djfI HYO GdeRGL hEjGc hGdYLdI hGMPQ GdEHWGA hGdZadI hGdSdGe JQTO Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3Jdjg aGFOI dLGHQ Hf MjGf ef cJGH GdMLQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdcjejGA h GdWHjYjGJs